Disease and treatment characteristics of polycythemia vera patients in Belgium: Results from a scientific survey. (7th February 2018) - Devos, Timothy; Beguin, Yves; Noens, Lucien; Van Eygen, Koen; Zachée, Pierre; Mineur, Philippe; Knoops, Laurent; Doyen, Chantal; Theunissen, Koen; Benghiat, Fleur Samantha; Reusens, Michael; Pluymers, Wim
Abstract: Objective: The current survey aimed to gather predefined disease parameters and treatment strategies to characterize the polycythemia vera (PV) patient population in Belgium. Methods: Cross‐sectional data from PV patients, seen at least once between May 2014 and May 2015 at 10 sites in Belgium, were collected in aggregated form and analyzed descriptively and quantitatively. Results: Data from 343 PV patients were collected. Of these, 174 (50.7%) were male and 256 (74.6%) were ≥60 years of age. Ninety‐two (26.8%) had a prior history of thrombotic events. Considerable proportions of patients had increased hematological parameters (hematocrit > 45% [31.2%], leukocytes > 10 × 10 9 /L [33.3%], and platelet > 400 × 10 9 /L [38.2%]). Most patients had non‐palpable spleen (284, 87.7%) and no phlebotomies during the past 6 months (197, 57.4%). Low‐dose aspirin was given as thrombosis prophylaxis in 249 (72.6%) patients, while 232 (67.6%) received hydroxyurea (HU) as cytoreductive treatment. Forty‐one patients (12.0%) were reported as resistant and/or intolerant to HU. Seventeen patients (5.0%) received ruxolitinib in the context of clinical trials. Conclusion: This survey provides better insight into the characteristics of Belgian PV patients and currently used treatment strategies. It shows that 232 (67.6%) PV patients continue to receive HU despite being potentially HU‐resistant.